Determinants of Polylepis (Rosaceae) Forest Distribution and Treeline Formation in the High Andes - Toivonen, Johanna M. (fi=Turun yliopisto|en=University of Turku|, 2014)
High elevation treelines are formed under common temperature conditions worldwide, but the functional mechanisms that ultimately constrain tree growth are poorly known. In addition to environmental constraints, the distribution of high elevation forests is largely affected by human influence. Andean Polylepis (Rosaceae) forests are an example of such a case, forests commonly growing in isolated stands disconnected from the lower elevation montane forests. There has been ample discussion as to the role of environmental versus anthropogenic causes of this fragmented distribution of Polylepis forests, but the importance of different factors is still unclear. In this thesis, I studied functional, environmental and anthropogenic aspects determining Polylepis forest distribution. Specifically, I assessed the degree of genetic determinism in the functional traits that enable Polylepis species to grow in cold and dry conditions. I also studied the role of environment and human influence constraining Polylepis forest distribution. I found evidence of genetically determined climatic adaptations in the functional traits of Polylepis. High elevation species had reduced leaf size and increased root tip abundance compared to low elevation species. Thus these traits have potentially played an important role in species evolution and adaptation to high elevation habitats, especially to low temperatures. I also found reduced photosynthesis rate among high elevation tree species compared to low elevation species, supporting carbon source limitation at treelines. At low elevations, Polylepis forest distribution appeared to be largely defined by human influence. This suggests that the absence of Polylepis forests in large areas in the Andes is the result of several environmental and anthropogenic constraints, the role of environment becoming stronger towards high elevations. I also show that Polylepis trees grow at remarkably low air and soil temperatures near treelines, and present new evidence of the role of air temperatures in constraining tree growth at high elevations. I further show that easily measurable indices of accessibility are related to the degree of degradation of Polylepis forest, and can therefore be used in the rapid identification of potentially degraded Polylepis forests. This is of great importance for the conservation and restoration planning of Polylepis forests in the Andes. In a global context, the results of this thesis add to our scientific knowledge concerning high elevation adaptations in trees, and increase our understanding of the factors constraining tree growth and forest distribution at high-elevation treelines worldwide.

El límite altitudinal arbóreo está formado bajo condiciones similares de temperatura a nivel mundial, pero los mecanismos funcionales que finalmente constriñen el crecimiento de los árboles son poco conocidos. Además de los factores ambientales, la distribución de los bosques de alturas está afectada por las acciones humanas. Los bosques andinos de Polylepis (Rosaceae) son un ejemplo de este caso: estos bosques crecen en rodales aislados y desconectados de los bosques montanos a menor altitud. Ha habido una amplia discusión sobre el rol de los factores ambientales y antropogénicos que causan esta distribución fragmentada de los bosques de Polylepis, pero la importancia de diferentes factores no está todavía clara. En esta tesis estudié los aspectos ecofisiológicos, ambientales y antropogénicos que pueden determinar la distribución de los bosques de Polylepis. Específicamente, evalué el grado del determinismo genético sobre las características ecofisiológicas que permiten a las especies de Polylepis crecer en condiciones frías y secas. Además, estudié el rol de los factores medio ambientales y antropogénicos que restringen la distribución de los bosques de Polylepis. Mis resultados dan evidencias de adaptaciones climáticos genéticamente determinadas en las características ecofisiológicas de las especies de Polylepis. Las especies de las zonas altas presentan hojas de tamaño reducido e incremento en la abundancia de ápices radiculares en comparación con las especies de las zonas más bajas. Estas características parecen haber desempeñado un rol importante en la evolución de las especies y en la adaptación a los hábitats de mayor altitud, especialmente a temperaturas bajas. Asimismo, encontré una tasa reducida de fotosíntesis en las especies de las zonas altas en comparación con las especies de las zonas más bajas. Esto apoya la hipótesis de limitación de adquisición de carbono en el límite altitudinal arbóreo. A menor altitud, la distribución de los bosques de Polylepis parece estar fuertemente afectada por las acciones antropogénicas. Esto sugiere que la ausencia de los bosques de Polylepis en la mayor parte de los Andes es el resultado de una serie de limitaciones ambientales y antropogénicas, donde el rol de los factores ambientales se incrementa hacia las zonas altas. También encontré que los árboles de Polylepis cerca del límite altitudinal arbóreo crecen a considerablemente bajas temperaturas del aire y del suelo. Además presento nuevas evidencias del rol de la temperatura del aire en la limitación del crecimiento de los árboles en las zonas altas. Adicionalmente, demuestro que los índices de accesibilidad que son fácilmente medibles están relacionados con el grado de degradación de los bosques de Polylepis y pueden ser aplicados para una identificación rápida de los bosques degradados. Esto es de gran importancia para la conservación y planificación de restauración de los bosques de Polylepis en los Andes. En el contexto mundial, los resultados de esta tesis contribuyen a incrementar el conocimiento científico relacionado a las adaptaciones de especies arbóreas en hábitats montañosos y el entendimiento de los factores que limitan el crecimiento de los árboles y la distribución de los bosques en el límite a altitudinal arbóreo a nivel mundial.

Vuoristopuurajat esiintyvät maailmanlaajuisesti samanlaisissa lämpötilaolosuhteissa, mutta puiden kasvua rajoittavat ekofysiologiset mekanismit tunnetaan kuitenkin huonosti. Ympäristöolosuhteiden lisäksi ihmisvaikutuksella on myös suuri merkitys vuoristometsien levinneisyyteen. Andien Polylepis-metsät ovat yksi esimerkki tällaisesta tapauksesta. Metsät kasvavat eristyneinä laikkuina alemman yhtenäisen vuoristometsävyöhykkeen yläpuolella. Ympäristöolosuhteiden ja ihmisvaikutuksen merkitystä Polylepis-metsien levinneisyydelle on tutkittu paljon, mutta eri tekijöiden merkitys metsien levinneisyydelle on edelleen epäselvä. Tutkin väitöskirjassani puiden ekofysiologiaan, ympäristöolosuhteisiin ja ihmisvaikutukseen liittyviä tekijöitä, jotka voivat selittää Polylepismetsien levinneisyyttä. Tulokseni osoittivat, että osa tutkimistani Polylepis-puiden ekofysiologisista piirteistä ilmensi geneettisesti määräytyneitä ilmastollisia sopeumia: korkean paikan lajeilla oli pienemmät lehdet ja enemmän juurenkärkiä kuin matalampien paikkojen lajeilla. Näillä piirteillä on todennäköisesti ollut tärkeä merkitys lajien evoluutiossa ja sopeutumisessa ylävuoriston elinympäristöihin, erityisesti mataliin lämpötiloihin. Tuloksieni mukaan korkean paikan lajeilla oli myös alentunut fotosynteesikapasiteetti matalampien paikkojen lajeihin verrattuna. Tämä tukee hypoteesia hiilen sitomiseen liittyvistä rajoitteista vuoristopuurajalla. Alemmilla korkeuksilla ihmistoiminnalla näytti olevan erityisen suuri merkitys Polylepis-metsien levinneisyyteen. Tuloksieni perusteella voidaan todeta, että Polylepis-metsien nykylevinneisyys on seurausta useasta eri ympäristöön ja ihmistoimintaan liittyvästä tekijästä, joista ympäristön merkitys levinneisyyden selittäjänä kasvaa siirryttäessä kohti ylävuoristoa. Tutkimustulokseni myös osoittivat, että Polylepis-puut kasvavat huomattavan alhaisissa lämpötilaolosuhteissa lähellä puurajaa, sekä ilman että maaperän lämpötilan suhteen. Lisäksi tulokseni osoittivat, että erityisesti ilman lämpötilalla on merkitystä puiden kasvulle vuoristossa. Havaitsin myös, että helposti mitattavat, metsien saavutettavuuteen perustuvat indeksit selittävät Polylepis-metsien rakennetta, ja näin ollen myös metsien kunnon heikkenemistä. Näitä indeksejä voidaan käyttää tunnistamaan nopeasti ja helposti alueita, joilla Polylepis-metsät ovat huonokuntoisimpia. Tällä tiedolla on merkitystä Polylepis-metsien suojelu- ja kunnostussuunnitelmille Andeilla. Väitöskirjatyöni tulokset lisäävät myös tietoa puiden sopeutumisesta vuoristo-olosuhteisiin ja auttavat ymmärtämään eri tekijöiden merkitystä puiden kasvulle ja metsien levinneisyydelle vuoristopuurajoilla maailmanlaajuisesti.